Optimising child development through smart education strategy in Pelemsewu Panggungharjo village - Yuliandari, Widya Rachmi; Anita, Ayu; Akmadi; Purwanta (LP2M Universitas Islam Negeri Mataram, 2024)
[Bahasa]: Prevalensi gangguan perkembangan pada anak meningkat di dunia dan diperkirakan mencapai 5-25% pada tahun 2019. Gangguan pertumbuhan dan perkembangan pada anak dapat mempengaruhi berbagai aspek perkembangan, termasuk perilaku, keterlambatan bicara dan bahasa, kesulitan koordinasi, dan gangguan kognitif. Perkembangan anak sangat dipengaruhi oleh stimulasi kognitif, sensitivitas pengasuh, dan kondisi sosial-ekonomi orang tua. Penelitian ini bertujuan untuk mengevaluasi efektivitas pendidikan kesehatan berbasis masyarakat dalam meningkatkan pengetahuan orang tua tentang stimulasi tumbuh kembang anak di Desa Panggungharjo, Yogyakarta. Metode pengambilan data yang digunakan meliputi wawancara, observasi, dan survei yang dipandu oleh kader posyandu di komunitas sebagai mitra. Intervensi pada pengabdian masyarakat ini meliputi sesi pendidikan, permainan, diskusi, dan stimulasi dengan 40 orang tua yang memiliki anak usia prasekolah. Analisis deskriptif digunakan untuk survei awal. Tes Wilcoxon mengukur pengetahuan orang tua pre-test dan post-test tentang perkembangan anak. Hasil penelitian menunjukkan adanya peningkatan signifikan dalam pengetahuan orang tua setelah intervensi, dengan rata-rata skor pre-test sebesar 8,1 meningkat menjadi 9,5 pada post-test (nilai Z = 13,79, p = 0,001). Temuan ini menggarisbawahi pentingnya pendidikan kesehatan yang menggunakan berbagai metode untuk meningkatkan pengetahuan orang tua, yang pada akhirnya dapat mengoptimalkan perkembangan anak. Studi ini menyimpulkan bahwa pendidikan kesehatan berbasis komunitas secara efektif meningkatkan pengetahuan dan keterampilan orang tua dalam merangsang tumbuh kembang anak. Intervensi ini dapat dijadikan model untuk program kesehatan anak di berbagai wilayah. Selain itu, media edukasi seperti booklet dapat membantu orang tua secara mandiri merangsang tumbuh kembang anak secara berkelanjutan. Dukungan dari profesional kesehatan dan keterlibatan aktif komunitas sangat penting untuk keberhasilan program ini. Kata kunci: gangguan perkembangan anak, edukasi kesehatan, mitra komunitas [English]: The prevalence of developmental disorders in children is increasing worldwide and is projected to reach a range of 5-25% by 2019. Children with growth and development abnormalities may experience a range of developmental challenges, such as behavioural issues, speech and language delays, coordination difficulties, and cognitive impairments. A child's growth is significantly impacted by cognitive stimulation, caregivers' sensitivity, and parents' socio-economic conditions. This study aimed to assess the efficacy of community-based health education in enhancing parents' understanding of child development stimulation in Panggungharjo Village, Yogyakarta. The data collection methods used included interviews, observations, and surveys guided by posyandu cadres in the community as partners. The interventions in this community service program involved education, games, discussions, and stimulation sessions with 40 parents of preschool-aged children. The intervention comprised educational activities, interactive games, group discussions, and stimulating sessions conducted with a cohort of 40 parents with preschool-age children. The baseline survey employed descriptive analysis. The Wilcoxon test was utilised to assess parents' knowledge of child development before and after the test. The findings demonstrated a significant improvement in parents' knowledge following the intervention, as indicated by the average pre-test score of 8.1, growing to 9.5 in the post-test (Z value = 13.79, p = 0.001). This discovery emphasises the significance of health education, which employs numerous approaches to enhance parental awareness and, consequently, enhance child development. The findings of this study indicate that community-based health education is a successful intervention for enhancing parents' knowledge and abilities in promoting child development. This strategy can potentially serve as a paradigm for child health programs in diverse settings. Furthermore, educational material, such as pamphlets, can assist parents in autonomously fostering sustainable child development. The success of this plan relies heavily on the support of health professionals and active community involvement. Keywords: child development disorders, health education, community as a partner